التناول المنهجي للدراسات السابقة وأساسياتها في المجال النفسي والاجتماعي - كروم، خميستي Karroum, Khemisti (جامعة عمار ثليجي بالأغواط - كلية العلوم الاجتماعية, 2015)
This article looks at the systematic approach of previous studies related to the following research - planned Accomplished - by a researcher at the psychological, and social fields depending on the specialty. And that by Taking the concept and fundamentals of previous studies and how to view and comment on them and using them to build research follows, referring to the difficulties to obtain. And proposals that will help the researcher to review the organization of previous studies.
يبحث هذا المقال في التناول المنهجي للدراسات السابقة ذات الصلة بالبحث الآتي– المزمع إنجازه من قبل الباحث- في المجالات النفسية والاجتماعية. وذلك من خلال تناول مفهوم وأساسيات الدراسات السابقة وكيفية عرضها والتعليق عليها وتوظيفها لبناء البحث الآتي، مشيراً إلى صعوبات الحصول عليها. ومقترحات تساعد الباحث على تنظيم مراجعته للدراسات السابقة.
Keywords: علم النفس -- علم الاجتماع -- مناهج البحث -- البحث العلمي